النظام الألكتروني لتسوية المدفوعات المالية دولية swift و كيفية استخدامه في البنوك الجزائرية - وفاء, ريغي; نور الأيمان, رمون (جامعة الوادي - University of Eloued, 2023)
" تتطلب عمليات التبادل التجاري الدولي تقنيات معينة تسوية الالتزامات المالية الناشئة في ما بين أطرافها تختلف عن تلك التقنيات المستعملة في عمليات التبادل التجاري المحلي، و ذلك لأن عمليات التبادل التجاري الدولي تنتابها عدة مشاكل و مخاطر مما قد يؤثر على السير الحسن لهذا النوع من المبادلات التجارية . من خلال هذه الدراسة سنحاول التطرق إلى مجموع التقنيات التسوية المستعملة في المبادلات التجارية الدولية، بما فيه وسائل وتقنيات التحويل وكذا تقنيات التمويل التي يمنحها النظام البنكي أو مؤسسات المالية المتخصصة بغية تسهيل وتنشيط حركة التبادل التجاري الدولي وإبراز مختلف الضمانات التي يمكن أن تقدمها هذه التقنيات لأطراف المبادلات التجارية الدولية . مع التركيز بصورة أساسية على نظام التحويل الإلكتروني swift بوصفه أهم وأكثر هذه تقنيات استعمال في نطاق المبادلات التجارية الدولية كما أن نظام سويفت تقنية تحكمها القواعد و الاعراف الدولة الموحدة للوحدات السلمية والصادرة عن غرفة التجارة الدولية التي تهدف إلى توحيد العمل بهذا النظام على المستوى الدولي إضافة إلى استعراض دراسة حالة على مستوى بنك الفلاحة والتنمية الريفية وكالة الوادي . الكلمات المفتاحية: نظام سويفت، تحويلات الإلكترونية، المبادلات الدولية ""International trade exchange operations require certain techniques to settle the financial obligations arising between their parties, which differ from those techniques used in local trade exchange operations, because international trade exchange operations suffer from several problems and risks, which may affect the good conduct of this type of trade exchange. Through this study, we will try to address the set of settlement techniques used in international commercial exchanges, including means and techniques of transfer, as well as financing techniques granted by the banking system or specialized financial institutions in order to facilitate and stimulate the movement of international trade exchange and highlight the various guarantees that can be provided. These technologies are for parties to international trade. Focusing mainly on the electronic transfer system (SWIFT) as the most important and most important of these techniques of use in the scope of international commercial exchanges. The SWIFT system is also a technology governed by the rules and customs of the unified state for peaceful units issued by the International Chamber of Commerce, which aims to unify the work of this system at the international level. In addition to reviewing a case study at the level of the Bank of Agriculture and Rural Development and eloued Agency. Keywords: Swift System, Electronic Transfers, International Exchanges "
Keywords: نظام سويفت، تحويلات الإلكترونية، المبادلات الدولية; Swift System, Electronic Transfers, International Exchanges